Cassava (Manihot esculenta Crantz): its nutritional composition insights for future research and development in Ethiopia - Abraham Woru Borku (Discover Sustainability)
Abstract Cassava (Manihot esculenta Crantz) plays an essential role in food security. Currently, cassava, which serves around 500 million people and relies on it as a primary carbohydrate source, making it the third largest source of carbs for human consumption in the world, is likely cassava. Despite its significance, compared to other African countries cassava’s production and research are notably underdeveloped in Ethiopia, a country where agriculture plays a crucial role in the economy. Hence, this review was conducted with the objective to assess the knowledge gap and recommend further studies for generating and documentation of information related to cassava. Cassava is an underutilized crop known for its high nutritional value, particularly in carbohydrates. This study employed a systematic literature review as a methodology to explore the nutritional composition of cassava and highlight potential areas for future research and development in Ethiopia. The review process involved several key stages to ensure comprehensiveness. Despite its rich nutrient profile and significant role in human health, as well as its social and economic importance, cassava has received insufficient attention from research and development efforts aimed at enhancing its contribution to Ethiopia’s food and nutrition security. The review shows that cassava root is composed almost exclusively of carbohydrate, as well as approximately 1–3% crude protein. The leaves have high protein, ranging from 16.6% to 39.9%, and mineral levels, as well as being a valuable source of vitamin B1, B2 and C and carotenes. Moreover, the available literature indicates a 100-g serving of boiled cassava leaves contains about 21% crude protein, along with 160 mg calcium, 2.6 mg iron, 2.0 mg zinc, and 1.7 mg niacin. The carbohydrate content of cassava is exceptionally high, highlighting its significance as a food source and presenting another potential area for research. Consequently, it is essential to carry out a thorough evaluation of cassava’s production, processing, and utilization within the community to optimize and fully harness this plant as a viable food source in Ethiopia.